Aspects of the Social Life of the City in Algeria during the Ottoman Period in the Writings of the English "Joseph Pitts" as a Model - djilali zourgui, Warda; khaldi, belarbi (The Algerian Historical Journal, 2026)
During the Ottoman period, Algeria witnessed conflicts with European powers due to its maritime activities in the Mediterranean. This led to the capture of many Europeans by Algerian corsairs,among the English captives Joseph Pitts who was captured in 1678 on his return from Newfoundland. During his captive in the city of Algiers, Pitts recorded many observations about life details there. After his return to England, he published a book entitled "A True and Faithful Account of the Religion and Manners of the Mohametans", which was issued in London in 1704. This source sheds light on various political, economic and social aspects of life in Algeria at that time. What caught my attention was his accurate recording of some social customs of the city's inhabitants, which prompted me to present these aspects to the reader in this article. These aspects include religious rituals of prayer, fasting and ablution, as well as prevailing social traditions in mourning ceremonies, people's greetings, eating habits, marriage, and other manifestations of life at that time.